PENGARUH KOMPETENSI DAN ADAPTIBILITAS TERHADAP KINERJA KARYAWAN DENGAN SELF EFFICACY SEBAGAI VARIABEL INTERVENING PADA KARYAWAN: (Pada PT. Kereta Api Indonesia Depo Lok SMC) - Elza Arindani Dwi Putri Aprilian; Heri Prabowo; Noni Setyorini (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This study aims to examine the influence of competence and adaptability on employee performance, with self-efficacy serving as an intervening variable among employees of PT KAI (Depo Lok SMC). The background of this research lies in the inconsistencies found in previous studies, indicating instability in perspectives within the existing literature on the topic. These differences highlight the need for further investigation to clarify the relationships among the variables being studied. The research adopts a quantitative method, with the population consisting of all employees of PT KAI (Depo Lok SMC). The study employs a saturated sampling technique, involving the entire population of 59 respondents. Data collection was conducted using a questionnaire designed to measure competence, adaptability, self-efficacy, and employee performance. The data collected were analyzed using the Structural Equation Modeling (SEM) technique, facilitated by the SmartPLS3 software. The findings reveal that competence has a positive impact on employee performance, while adaptability does not significantly affect performance. Additionally, competence positively influences self-efficacy, and adaptability also shows a positive effect on self-efficacy. However, self-efficacy does not have a direct impact on employee performance. Furthermore, the study found that competence and adaptability do not influence employee performance when mediated by self-efficacy. These results provide new insights into the critical role of competence in directly enhancing performance, while self-efficacy is not strong enough to act as a mediating variable. This study contributes to the existing literature by offering a deeper understanding of the relationships between competence, adaptability, self-efficacy, and employee performance.